Are endothelial progenitor cells a prognostic factor in patients with heart failure?. (February 2012) - Alba, Ana Carolina; Delgado, Diego Hernan; Rao, Vivek; Walter, Stephen; Guyatt, Gordon; Ross, Heather Joan
For the last two decades, endothelial progenitor cells (EPCs) have been proposed as a novel prognostic marker and potential therapeutic target in patients with cardiovascular diseases. EPCs are involved in the process of adult vasculogenesis and repair of dysfunctional endothelium. Endothelial dysfunction has been documented in the peripheral and coronary arteries of chronic heart failure (HF) patients, and has proved to be an independent predictor of morbidity and mortality in HF patients. This has led researchers to analyze the association of EPCs and disease severity in HF patients. In this paper, we review studies analyzing the prognostic role of EPCs in patients with HF. Through a systematic search, we identified 14 relevant studies. Only one study analyzed mortality as an outcome; the others evaluated the association between EPC levels and patients'' characteristics. Overall, results were inconsistent and suggested that levels of EPCs may vary according to factors such as disease severity, underlying cause of cardiomyopathy and medical therapy.